Re-evaluating Our Knowledge of Health System Resilience During COVID-19: Lessons From the First Two Years of the Pandemic - Dell D. Saulnier; Anna Duchenko; Sierra Ottilie-Kovelman; Fabrizio Tediosi; Karl Blanchet (Kerman University of Medical Sciences, 2023)
Background  Health challenges like coronavirus disease 2019 (COVID-19) are becoming increasingly complex, transnational, and unpredictable. Studying health system responses to the COVID-19 pandemic is an opportunity to enhance our understanding of health system resilience and establish a clearer link between theoretical concepts and practical ideas on how to build resilience. Methods  This narrative literature review aims to address four questions using a health system resilience framework: (i) What do we understand about the dimensions of resilience? (ii) What aspects of the resilience dimensions remain uncertain? (iii) What aspects of the resilience dimensions are missing from the COVID-19 discussions? and (iv) What has COVID-19 taught us about resilience that is missing from the framework? A scientific literature database search was conducted in December 2020 and in April 2022 to identify publications that discussed health system resilience in relation to COVID-19, excluding articles on psychological and other types of resilience. A total of 63 publications were included. Results  There is good understanding around information sharing, flexibility and good leadership, learning, maintaining essential services, and the need for legitimate, interdependent systems. Decision-making, localized trust, influences on interdependence, and transformation remain uncertain. Vertical interdependence, monitoring risks beyond the health system, and consequences of changes on the system were not discussed. Teamwork, actor legitimacy, values, inclusivity, trans-sectoral resilience, and the role of the private sector are identified as lessons from COVID-19 that should be further explored for health system resilience. Conclusion  Knowledge of health system resilience has continued to cohere following the pandemic. The eventual consequences of system changes and the resilience of subsystems are underexplored. Through governance, the concept of health system resilience can be linked to wider issues raised by the pandemic, like inclusivity. Our findings show the utility of resilience theory for strengthening health systems for crises and the benefit of continuing to refine existing resilience theory.